ANALISIS DIGITAL MARKETING DALAM MENINGKATKAN VOLUME PENJUALAN PRODUK HIDROPONIK (STUDI KASUS: PERKEBUNAN VALEFARM HIDROPONIK SOLO) - Kusumawati, Dinda; Utomo, Yuni Prihadi (Universitas Muhammadiyah Surakarta, 2025)
Digital marketing is a marketing activity that uses promotional strategies via the internet that can expand the sales scale and is not expensive to carry out. The use of digital marketing aims to increase purchasing power for products. The aim of writing this publication manuscript is to find out the impact of digital marketing on increasing sales at the Valefarm Hydroponic Plantation in Surakarta. This research was carried out using the Participatory Research method. This method is designed to involve the actors involved in each stage of the research, ensuring the desirability and relevance of the research. Active participation here is by being directly involved in digital marketing activities. This digital marketing activity is through an internship at Valefarm Hidroponik Surakarta. The use of digital marketing at Valefarm Hidroponik Surakarta uses platforms including Instagram, Tiktok, YouTube and websites. This research provides in-depth insight into the success of digital marketing in increasing sales volume through the active participation of researchers. The findings of this research not only support increasing sales volumes but also provide a basis for developing digital marketing in accordance with market needs. The Participatory Research approach has proven to be an effective tool in understanding and improving economic competitiveness in the context of hydroponic farming.